2018
DOI: 10.1088/1361-6382/aac588
|View full text |Cite
|
Sign up to set email alerts
|

The degrees of freedom of area Regge calculus: dynamics, non-metricity, and broken diffeomorphisms

Abstract: Discretization of general relativity is a promising route towards quantum gravity. Discrete geometries have a finite number of degrees of freedom and can mimic aspects of quantum geometry. However, selection of the correct discrete freedoms and description of their dynamics has remained a challenging problem. We explore classical area Regge calculus, an alternative to standard Regge calculus where instead of lengths, the areas of a simplicial discretization are fundamental. There are a number of surprises: tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 185 publications
0
39
0
Order By: Relevance
“…Previous investigations [17,18] only allowed for quasilocal fluctuation of the metric which are, in the semiclassical limit, expected to turn to gauge degrees of freedom. It can be expected that these appear in the theory as spurious degrees of freedom, since it is well-known that the gauge symmetry of GR is broken in the EPRL model [45,73,77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations [17,18] only allowed for quasilocal fluctuation of the metric which are, in the semiclassical limit, expected to turn to gauge degrees of freedom. It can be expected that these appear in the theory as spurious degrees of freedom, since it is well-known that the gauge symmetry of GR is broken in the EPRL model [45,73,77].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in [45], it was observed that the EPRL model breaks vertex displacement symmetry, which is the manifestation of diffeomorphisms on the lattice [45,[73][74][75][76][77]. While this breaking of symmetry is well-known in classical Regge calculus, where it appears whenever curvature is involved, the quantum theory breaks it even in the case of flat metrics.…”
Section: A One Dimensional Isochoric Rg Flowmentioning
confidence: 99%
“…To this end, one uses versions of Regge calculus based on other sets of variables than the edge lengths, e.g. areas and angles [41,45,69,81]. Another choice, possibly more suited for Lorentzian signature, would be variables related to spinors or twistors [82,83].…”
Section: Discussionmentioning
confidence: 99%
“…Turning on curvature, for instance by changing the boundary data, these eigenvalues will no longer vanish and will scale with the amount of curvature, as determined by the deficit angles [37,38]. A similar effect arises in the presence of torsion [45].…”
Section: Regge Calculusmentioning
confidence: 99%
“…The states are peaked on homogeneous geometries. These geometries are however generalized in the same way as the standard loop quantum gravity geometries are, if understood in terms of piecewise flat simplicial building blocks [76][77][78][79][80].…”
Section: Discussionmentioning
confidence: 99%